MEN`S PHYSICAL, PSYCHOLOGICAL AND SOCIAL RESPONSE TO VASECTOMY ACCEPTOR OF FAMILY PLANNING PROGRAM IN SUKOHARJO CENTRAL JAVA - Winarsih Nur Ambarwati (Universitas Airlangga, 2017)
Introduction: Indonesia is on the fourth position in the world as the most populated nation in 2009. Great number of people with lack of skill would give potential burden in the nation development. Generally, the outcome of Indonesian Family Planing Program(FPP) acceptor to Indonesian women is sufﬁcient which is ranging to 59 percent of the total 60,3 percent of participants but if compared to men's participation in is still insigniﬁcant. Husband's participation as participant is still low 1.3% consisted of 0.9 percent condom user, 0.4 percent vasectomy user. To describe experiences of Indonesian men following vasectomy in relation to their physical, psychological and social responses to vasectomy. Method: The research design of this research uses descriptive qualitative study. The sample selection was done using theoretical sampling technique. The data collection instrument of grounded theory research is the researcher herself, while other instruments are namely ﬁeld report, audiotape, videotape, and notes. The data analysis is utilized Colaizzi`s method. Result: Numbers of participants were 7 persons. Physical change after the vasectomy surgery is on general physical change (there is no change felt, the body's stamina raises, healthier, less energy, or weary) and physical change on reproduction organ is none. Sexual ability has no change, it increases, it also decreases. The sexual satisfaction is the same, more satisﬁ ed, or less satisﬁed. The characteristic change of spermatid is the same, there is change (lesser quantity, more dissolved), and ignore it. All participants said that they feel more comfortable in doing sex after vasectomy surgery. Most participants feel conﬁdence of their sexual ability. The participants' perspective had no difference and feel difference, or there is a change. Most participants stated that vasectomy is the right decision, but few felt disappointed. The social environment response toward men as the acceptor of vasectomy is that the society support it and few contradict it. Discussion: vasectomy no hazard to physic, psycology, social, and wife. Vasectomy is a good one of methode contraception to men.